OPTIMALISASI TEKNOLOGI DIGITAL DALAM AKTIVITAS PUBLIC RELATIONS - Putra Chaniago; Siti Osa Kosassy; Yenni Jufri; F Yasmeardi; Mukti Diapepin (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the role of Public Relations in an institution as a strategy to build the institution's image by optimizing the function of digital technology. Public relations should have a wide network and relationships to be able to convey information, education and promotions. However, along with developments in technology and the flow of information in society, public communication activities carried out by Public Relations also experience various challenges that must be faced. Challenges in public communication include competition in facing the digitalization of information in the form of using the internet in communication activities. Therefore, to fulfill the role and function of government public relations as a public communicator, this challenge also becomes an opportunity as a means of carrying out the main function of public relations by optimizing digital technology. In this article, the author conducted research aimed at finding out how to optimize digital technology in public relations activities. The type of research in this article is descriptive qualitative. The results of this research show that the Pariaman City Government optimizes digital technology in carrying out the main public relations functions of the Pariaman City Government including, (1) in disseminating information about government policies and programs; (2) Performing services to the public; and (3) Bridging the interests of the institution and the public by accommodating aspirations and paying attention to public desires.